The Role Of Forensic Experts In Aircraft Accident Investigations: A Multidisciplinary Review - Monisha, R; Kumar Meena, Sachin; Jyothsna Devi, P V; Alwin A, Sherley (Journal of Forensic Medicine and Toxicology, 2026)
Aviation disasters, while infrequent, result in high mortality and complex investigative challenges that demand a mul tidisciplinary forensic approach. Forensic experts play a pivotal role in identifying victims, analyzing injury patterns,  collecting toxicological evidence, and contributing to crash reconstruction. The recent Air India Flight 171 crash in  Ahmedabad, which resulted in 260 deaths, has brought renewed attention to the critical but often overlooked role of  forensic science in aviation disaster response in India. Despite its importance, aviation forensics remains one of the least  explored areas within forensic medicine, especially in low- and middle-income countries. This review aims to consolidate  the current practices, competencies, and technological advances in aviation forensic investigations, while emphasizing  the need for national preparedness, standardization, and training.
Keywords: Aircraft accident; Disaster victim identification; Aviation safety; DNA profiling